Persamaan Bahasa minang dan kerinci dari segi fonetik - Dika, Palen; Rohanda, Rohanda; Fauziah, Isma; Halim, Muhammad Abdul (Innovative: Journal Of Social Science Research, 2023)
The aim of this article is to investigate the phonetic similarities between the Minang and Kerinci languages, with a specific focus on their phonetic analysis. Minang and Kerinci are two languages originating from Indonesia, each spoken by distinct ethnic groups. However, there are intriguing phonetic similarities between these languages that can contribute to a better understanding of linguistic relationships in the western part of Indonesia. This study employs phonological analysis methods to identify these phonetic similarities and their meanings in both languages. The results of this analysis provide profound insights into shared phonetic elements. This research can significantly contribute to understanding the linguistic connections between Minang and Kerinci, unveiling their intertwined historical linguistic roots. Moreover, it can be beneficial in the context of education and the preservation of regional languages in Indonesia. This article illustrates the importance of phonological studies in dissecting the elements of language and identifying inter-language relationships in complex geographical regions such as Indonesia. Kata kunci : Bahasa Minang, Bahasa kerinci , fonologi , fonem , analisis fonologi , linguistik, Indonesia.